Analysis of the 11P Marketing Mix Strategy in the Healthy Food Catering Business - Ridwan, Okky Rizal; Ningsih, Caria (Universitas Pendidikan Indonesia, 2021)
Many Micro, Small and Medium Enterprises (MSMEs) have sprung up in Indonesia, but their growth is inconsistent and tends not to last long in the long term, and ultimately fails in the market. This research was conducted on the Easy Fit Kitchen healthy food catering business, which is one of the healthy food catering businesses that is being favored by the community in Bogor. The technique used in this research is a qualitative descriptive method with a business study that is being carried out. Researchers analyze the marketing mix of the Easy Fit Kitchen business using 11P analysis including Product, Price, Promotion, Place, People, Partnership, Process, Packaging, Programming, Possibility, and Position. The results show that all 11P aspects have been applied in business and the possibility aspect is useful for analyzing future possibilities that will be faced by the healthy food catering business. It is found that based on the marketing mix strategy that is carried out, the business must keep up with the times, product and service innovation, the promotions must be wider in scope, the cooperation can reach aspects that have not been touched, and in the future the business is expected to open branches in other places